2019
DOI: 10.1186/s12879-019-4360-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and epidemiology of Genogroup II noroviruses in children with acute sporadic gastroenteritis in Shanghai, China, 2012–2017

Abstract: Background Noroviruses (NoVs) are considered an important cause of acute gastroenteritis (AGE) across all age groups, especially in children under 5 years of age. We investigated the epidemiology of noroviruses in outpatient children from the Children’s Hospital of Fudan University in Shanghai, China. Methods Stool specimens were collected between January 2012 and December 2017 from 1433 children under 5 years of age with acute gastroenteritis. All samples were analysed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 53 publications
(66 reference statements)
5
24
0
Order By: Relevance
“…We also observed that norovirus infection was found extensively in children <2 years old, with a significantly higher prevalence compared to that among children ≥2 years old (P = 0.01). Although norovirus infection occurred in all age groups, the children <2 years old appeared to be more vulnerable, which is consistent with other reports (Wu et al, 2020;Louya et al, 2019;Lu et al, 2019;Siafakas et al, 2018). The low prevalence of norovirus infection among older children could be due to acquired immunity through previous exposures (Gupta et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also observed that norovirus infection was found extensively in children <2 years old, with a significantly higher prevalence compared to that among children ≥2 years old (P = 0.01). Although norovirus infection occurred in all age groups, the children <2 years old appeared to be more vulnerable, which is consistent with other reports (Wu et al, 2020;Louya et al, 2019;Lu et al, 2019;Siafakas et al, 2018). The low prevalence of norovirus infection among older children could be due to acquired immunity through previous exposures (Gupta et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The low prevalence of norovirus infection among older children could be due to acquired immunity through previous exposures (Gupta et al, 2018). Norovirus GII infections were predominant, representing 97.5% of the total norovirus infections, which is consistent with studies from other parts of Indonesia and other countries (Athiyyah et al, 2019;Lu et al, 2019;Mathew et al, 2019;Nirwati et al, 2019;Wang et al, 2019). GII noroviruses are more closely related to diseases that require medical treatment, whereas GI noroviruses result in mild symptoms and do not require hospitalization (Siafakas et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Up to now, noroviruses are phylogenetically classified into 10 genogroups (GI-GX) and, among them, at least five genogroups (GI, GII, GIV, GVIII and GIX) could infect humans [ 5 ]. GII.3 is a common cause for sporadic infection in infants and children as the second major genotype after GII.4 in China [ 6 , 7 ]. To date, more reports focus on norovirus genotypes, such as GII.2[P16], GII.4, and GII.17[P17], that cause outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…ORF 3 encodes a minor structural protein [9]. In spite of the large genetic diversity of norovirus, it is noteworthy that norovirus of the genotype GII.4 are responsible for a majority of infections [10,11].…”
Section: Norovirus Genome and Genetic Diversitymentioning
confidence: 99%